2007
DOI: 10.1111/j.1471-0528.2007.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety versus success in elective single embryo transfer: women’s preferences for outcomes of in vitro fertilisation

Abstract: Objective To assess whether women waiting to undergo in vitro fertilisation (IVF) view adverse outcomes associated with twin pregnancy as more desirable than having no pregnancy at all.Design Women's preference values for five adverse birth outcomes associated with twin pregnancy were compared with their preference value for treatment failure (TF), i.e. no pregnancy at all.Setting Aberdeen Fertility Centre, University of Aberdeen, UK.Population A total of 74 women waiting to undergo IVF.Methods The standard ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Child et al 21 found that 41% of women having assisted reproductive technology were actually inclined to prefer a twin pregnancy, and some women waiting for IVF treatment viewed severe child disability outcomes more desirable than having no child at all. 22 This barrier might be overcome by providing educational material to women so as to improve their knowledge on outcomes and risks of multiple pregnancies. 23 The feasibility of eSET also relies on improving outcomes with cryopreserved embryos and the technique on vitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Child et al 21 found that 41% of women having assisted reproductive technology were actually inclined to prefer a twin pregnancy, and some women waiting for IVF treatment viewed severe child disability outcomes more desirable than having no child at all. 22 This barrier might be overcome by providing educational material to women so as to improve their knowledge on outcomes and risks of multiple pregnancies. 23 The feasibility of eSET also relies on improving outcomes with cryopreserved embryos and the technique on vitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence to support that infertile women weigh treatment success more than the chances of future risks [17]. In a recent literature search noted that twin gestations following IVF represent both a favorable treatment outcome that should be encouraged, in contrast to the current medical consensus [18].…”
Section: Discussionmentioning
confidence: 99%
“…40 We assumed that a successful healthy birth outcome would return women to the age-specific UK population norm, whereas giving birth to a child with a disability would be associated with an EQ-5D utility decrement of 0.07. 41 For women suffering a stillbirth or neonatal/infant death followed by no subsequent pregnancy, we applied a utility weight of 0.543 elicited directly from infertile women in Grampian, 42 because no general population preference weights were available for this outcome.…”
Section: Utility Weightsmentioning
confidence: 99%
“…42 In this previous study, standard gamble utility weights were elicited for: 'premature delivery/neonatal admission'; 'giving birth to a child with disability'; 'experiencing a neonatal death followed by no subsequent pregnancy'; and 'treatment failure' followed by life-long childlessness.…”
Section: Utility Weightsmentioning
confidence: 99%
See 1 more Smart Citation